Case Report: Huge inclusion cyst as a long term complication of female genital mutilation - Raymond Takpe; Oluwasomidoyin Olukemi Bello; Chinedum A.C Onebunne (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2019)
Female genital mutilation (FGM) is a common practice in Nigeria and is performed for religious and cultural reasons despite associated short- and long-term complications. Epidermoid inclusion cyst of the external genitalia is one of its late complications. We describe the successful management of a huge painless vulva mass measuring 10cm by 8cm in a 40-year-old woman. She had excision of the cyst with histological diagnosis of epidermal inclusion cyst. There is need for medical practitioners to have a high index of suspicion of epidermal inclusion cyst for vulva swelling especially in Nigeria where FGM is prevalent. However, public enlightenment and enforcement of laws on eradication of FGM as well as management of its complications are crucial.